Interactive Simulation of SysML Models using Modelica - Parham Vasaiely (2009)
The International Council on Systems Engineering (INCOSE) identified Model-Based Systems Engineering as a key driver for effective and efficient system development in the future. System simulation using models is widely used for analysis, communication or training purposes. This thesis presents an approach for user-interactive simulation of system models which are created using the graphical Systems Modelling Language (SysML) and translated into executable Modelica models. A software prototype based on the OpenModelica environment will be developed and demonstrates the application on a concrete example.